Practice cases for digital pedagogy olympiad assignments - O. V. Gordienko; A. A. Sokolova; O. A. Ivanov; V. V. Fyodorov (Вестник Северо-Кавказского федерального университета, 2023)
One of the tasks of a teacher in connection with global changes in the surrounding reality (universal digitalization: digital government, digital medicine, digital economy, digital education, etc.) is to find a place in the new world for each member of society, that is, socialization in the digital world, as well as the formation of digital literacy among citizens, including digital consumption (the number of personal contacts in social networks, personal gadgets, possession of digital technologies and tools, etc.), digital competencies (search for information; use of mobile devices, social networks; production of content, etc.), digital security (protection of personal data, combating threats, including fakes and viruses; attitude to piracy content; the level of culture of interaction in social networks, etc.). The formation of a highly qualified teacher capable of becoming the head of transformational processes is one of the priority tasks of pedagogical education. The article is devoted to the description of practical cases, criteria and principles for the student Olympiad in digital pedagogy in a distance format. The described types of tasks are aimed at checking the level of digital literacy of the future teachers themselves, as well as their potential as teachers who are able to develop the digital literacy of their students in their daily professional activities. For clarity, the paper presents statistical data of the Olympiad «Pedagogical Digitalization», organized in 2019–2022. Institute for the Development of Digital Education of Moscow Pedagogical State University.